1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Subtraction of Logarithm

  1. Jan 6, 2012 #1
    1. The problem statement, all variables and given/known data
    If [tex]\tilde{G_n}(\theta,\lambda)= \sum_{k=1}^{n} \tilde{g_(k,1)}(i\lambda)\frac\{{theta}^{k}}{k!}[/tex], show that [tex]log(1-\frac{\tilde{G}(\theta,\lambda)\lambda}{\lambda-i2{\phi}'(\theta)})-log(1-\frac{\tilde{G}_n(\theta,\lambda)\lambda}{\lambda-i2{\phi}'(\theta)})=log(1-\frac{\lambda}{\lambda-i2{\phi}'(\theta)}\frac{\tilde{G_n}(\theta,\lambda)-\tilde{G}(\theta,\lambda)}{1-\tilde{G_n}(\theta,\lambda)\lambda(\lambda-2i\phi'(\theta))^{-1}})[/tex]


    2. Relevant equations

    log(a/b)=log(a)-log(b)

    3. The attempt at a solution

    Using the property of log, I came up with [tex]log(\frac{\lambda-2i\{phi}'(\theta)-\tilde{G}(\theta,\lambda)\lambda}{\lambda-i2{\phi}'(\theta)-\tilde{G_n}(\theta,\lambda)\lambda})[/tex] but it's not really equal as you can see.
     
    Last edited: Jan 6, 2012
  2. jcsd
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Can you offer guidance or do you also need help?



Similar Discussions: Subtraction of Logarithm
Loading...